2014
DOI: 10.1158/2159-8290.cd-13-1007
|View full text |Cite
|
Sign up to set email alerts
|

The Immune Microenvironment Confers Resistance to MAPK Pathway Inhibitors through Macrophage-Derived TNFα

Abstract: Recently the rationale for combining targeted therapy with immunotherapy has come to light, but our understanding of the immune response during MAPK pathway inhibitor treatment is limited. We discovered that the immune-microenvironment can act as source of resistance to MAPK pathway-targeted therapy, and moreover during treatment this source becomes reinforced. In particular, we identified macrophage-derived TNFα as a crucial melanoma-growth factor that provides resistance to MAPK pathway inhibitors through th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
193
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(206 citation statements)
references
References 50 publications
8
193
1
4
Order By: Relevance
“…In addition, emerging therapies for the treatment of melanomas, such as anti-CTLA4 (50), and BRAF V600E inhibitors (7,8), are associated with CD8 þ T-cell immune response and TNF production, even in patients with disease progression. Macrophage-derived TNF is important for BRAF V600E melanoma growth in vivo and confers resistance to MAPK pathway inhibitors (16). Whether a combination of anti-TNF and emerging therapies may exert a clinical benefit by enhancing CD8 þ T-cell-dependent immune response toward melanoma remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, emerging therapies for the treatment of melanomas, such as anti-CTLA4 (50), and BRAF V600E inhibitors (7,8), are associated with CD8 þ T-cell immune response and TNF production, even in patients with disease progression. Macrophage-derived TNF is important for BRAF V600E melanoma growth in vivo and confers resistance to MAPK pathway inhibitors (16). Whether a combination of anti-TNF and emerging therapies may exert a clinical benefit by enhancing CD8 þ T-cell-dependent immune response toward melanoma remains to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Similar data have been obtained by injecting anti-TNF-neutralizing antibodies (14) or soluble TNF-R1 (15), indicating that TNF blockade may represent a useful strategy to prevent melanoma metastasis. A recent study showed that TNF deficiency can delay tumor growth in a spontaneous mouse model of BRAF V600E melanoma (16). In humans, whereas different case reports have documented the occurrence of melanoma in patients with autoimmune disorders treated with anti-TNF, recent meta-analyses did not confirm the association of anti-TNF treatments and an increased melanoma incidence (17)(18)(19)(20).…”
Section: Introductionmentioning
confidence: 99%
“…This resistance mechanism can be overcome by combining MEK inhibitors with an inhibitor of NF-κB signaling to prevent TAM accumulation and TNF secretion in tumors. Interestingly, TNF expression is independent of the state of TAM polarization in this model, as all cultured macrophages expressed TNF regardless of the stimuli used in vitro to skew their polarization [106]. By contrast, TAM polarization may be important for the response to targeted therapies in other cancer types and can even result in adverse effects.…”
Section: Innate Immune Cellsmentioning
confidence: 80%
“…In mice bearing melanoma cell lines derived from Braf V600E ;Tyr::CreERT2 tumors, the release of TNF by TAMs protects tumors from MEK inhibitor-induced cell death [106]. This resistance mechanism can be overcome by combining MEK inhibitors with an inhibitor of NF-κB signaling to prevent TAM accumulation and TNF secretion in tumors.…”
Section: Innate Immune Cellsmentioning
confidence: 99%
“…Although less characterized than tumor macrophages and IL-17-producing T cells 12,13 , neutrophils are also emerging as important players in the pathophysiology of cancer. [14][15][16] Neutrophils are the most abundant leukocytes and serve as essential effector cells in the first line of host defense against invading microorganisms.…”
Section: Introductionmentioning
confidence: 99%